(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this study was to investigate the effects of sports stressors and academic performance of student-athletes in selected colleges of education in Ghana. The study was guided by two (4) specific objectives: (a) To assess the influence of sporting stress on the academic performance of student-athletes in Colleges of Education in Ghana; (b) To compare the GPA of student-athletes in the year of competitive sports and the year of no competitive sports in the Colleges of Education in Ghana and (e) to recommend ways of managing stress to enhance student athlete’s academic performance. The study adopted a cross-sectional survey design, in which both quantitative and qualitative data were collected. The study was conducted in Ghana. Simple random sampling was used to select student-athletes while purposive sampling was used to select tutors. The target population for this study was 12 tutors and 768 student-athletes in six (6) Ghana Colleges of Education. The total sample size for the study was 335 (12 tutors & 323 students-athletes). The instruments for data collection were a questionnaire, an interview guide and document analyses. Both, descriptive and inferential statistical analyses were done using Statistical Package for Social Sciences (SPSS version 20). Descriptive statistics summarized, organized and described the responses when addressing study objectives through the use of means, standard deviations, frequencies, and percentages. Inferential statistics such as ANOVA and Point biserial were used to test the formulated null hypotheses. All hypotheses were tested at p<0.05 alpha level of significance. The study found that competitive sports stressors have a statistically significant influence on the academic performance of student-athletes in colleges of education in Ghana. The study also revealed that competitive sports stress has a statistically significant influence on the academic performance of student-athletes, especially the females, in colleges of education in Ghana. This study therefore, recommends that female student-athletes be given scholarships to motivate and enhance other female students’ participation in competitive sports. The study also recommends that colleges of Education in Ghana introduce stress management strategies to address stressors’ link to academic performance of student-athlete.